Two-phase pressure drop analysis of swirl tube in one-side high heat load condition for plasma facing component application. (30th August 2021) - Lim, Ji Hwan; Lee, Su Won; Hwang, Donkoan; Oh, Hoongyo; Park, Minkyu; Kim, Moo Hwan; Jo, HangJin
Abstract: In this study, the two-phase pressure drop of a one-side heated swirl tube (twist ratio = 3, 5) was experimentally studied. If the a heat flux is gradually increased, the vapor blocks the flow path, thus leading to an increase in the differential pressure. As the inset sub-cooling and mass flow rate increase, the vapor is removed by condensation more rapidly, and thus, the rate of increase of differential pressure is reduced. From the evaluation of the prediction performance of the existing two-phase pressure drop correlations, it was found that the mean error rates of all correlations exceeded 50%. This is because most of the existing correlations were not developed based on the microchannel, but they were not focused on the swirl tube. Therefore, the authors developed a new two-phase pressure drop multiplier correlation for a one-side heated swirl tube that reflects the effect of the twist tape by modifying the Manglick single-phase swirl tube pressure drop correlation using the AI regression method.